2019
DOI: 10.1111/exd.13951
|View full text |Cite
|
Sign up to set email alerts
|

Dermoscopic similarity is an independent predictor of BRAF mutational concordance in multiple melanomas

Abstract: Background The association of clinical and dermoscopic features with BRAF mutational status has been poorly analysed in multiple primary melanomas (MPM). Objective To investigate whether concordance of BRAF mutational status is associated with dermoscopic similarity in multiple melanomas of the same patient. Methods Dermoscopic images and corresponding tissue sections of 124 melanomas from 62 patients with MPM were selected at four Italian Dermatology Departments. Similarity of dermoscopic appearance between m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 27 publications
(56 reference statements)
0
3
0
Order By: Relevance
“…Moscarella et al reported a concordance rate respectively in 53.0% and 38.7% of MPMs 8 . Colombino et al reported a higher concordance rate (66.7%) but limited to only 12 patients.…”
Section: Figurementioning
confidence: 94%
“…Moscarella et al reported a concordance rate respectively in 53.0% and 38.7% of MPMs 8 . Colombino et al reported a higher concordance rate (66.7%) but limited to only 12 patients.…”
Section: Figurementioning
confidence: 94%
“…Dermoscopic features may also overlap in lesions with similar pathologic origin. A percentage (38.7%) of patients with multiple primary melanomas were found to have similar dermoscopic features, and these melanomas showed 5.7x higher odds to share the same BRAF mutational status [ 17 ]. However, dermoscopy, like all imaging techniques, has its limitations.…”
Section: Reviewmentioning
confidence: 99%
“…MSI was described in displastic naevi, MMs and MM metastases, suggesting that the MMR system and consequently MSI could contribute to the pathogenesis of MM (17). Differently to colon cancer and other solid malignancies that are treated with immunotherapy (1,18,19), potential IHC biomarkers are still limited for MM up to now. This lack of predictive biomarkers for immunotherapy response in MM patients is today an important field of investigation, whose aim is to allow a personalized therapeutic approach.…”
Section: Introductionmentioning
confidence: 99%